Architectural rendering of the Agriculture Building, Alaska Yukon Pacific Exposition, Seattle, 1908 - Nowell, Frank H., 1864-1950 (1908)
Photograph of an architectural rendering. Caption on image: Agricultural Building, Alaska-Pacific-Yukon Exposition. Graham and Myers, Architects PH Coll 727.160 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number